Practical Applicability of Teledentistry in Pediatric Patients Amidst Pandemic : A Narrative Review - Goswami, Mousumi; Nangia, Tanu; Saxena, Aditya; Chawla, Sakshi; Mushtaq, Anam; Singh, Shrey R.; Jain, Palak (Frontiers in Dental Medicine, 2021)
Outbreak of COVID-19 pandemic has imposed a situation where all the healthcare facilities except emergency services remain suspended. These times generated the necessity for implementation of a health-care delivery system that can be accessed digitally and thus benefit majority of children as well as the health-care professionals . This review aims to propose a sound model of less technique sensitive, safe and handy strategies regarding dental traumatic injuries, endodontic and restorative concerns as well as orthodontic urgencies till the complete clinical help can be sought. 529 articles were obtained from PubMed, Google Scholar, Embase, Lilacs and Cochrane databases published from 2011 to 2021. 19 articles that described teledentistry in covid era were included. Teledentistry can therefore serve as a vital patient management strategy that aids in triaging urgent and elective patient treatment needs, ultimately easing the burden of clinics and at the same time providing a safer means of consultation.